A Goddess with Bird’s Claws: An Exploration of the Image of Magu - Geng, Qiongke (Religions, 2023)
In China, Magu is a household name for a female Daoist immortal. As a symbol of longevity, people believe that she can prolong their lives and bring them good luck. This paper takes the fact that Magu has hands that look like birds’ feet as a clue to sort out the evolution of the image of Magu. In this article, it is argued that the prototype for the image of the Daoist immortal, Magu, is the bird goddess of the Neolithic goddess and that Magu’s hands, which look like bird claws, are a symbol of the goddess’s divine power. After entering the patriarchal society, the figure of Magu was eroticized and her hands, which represented divine power, became a tool for men to scratch their backs. Daoism, however, inherited the matriarchal society’s worship of women and retained the image of Magu with her hands that resembled the feet of a bird. When Daoism incorporated Magu into its system of deities, the image of Magu was remodeled to conform to the teachings of Daoism, thus making Magu a beautiful, kind-hearted immortal with high moral sentiments.